Exploring the Role of Problem-Based Learning in Developing Conflict Resolving and other Soft Skills - A Quasi-Experimental Study - Deep, Sadia; Salleh, Berhannudin Mohd; Othman, Hussain (International Review of Management and Marketing, 2016)
Problem-based learning is widely regarded as a successful and innovative method of instruction for skills development in the recent decades. This empirical study therefore, intends to explore the perception of employees and assess the impact of three days PBL approach based training on the soft skills and traits of employees. A mixed method research approach was used for the study; the data for the study therefore, emerged from the semi-structured interviews, 53 items based survey, and observation of the training process. The employees belonging to the three development organizations from the area of Islamabad and Peshawar in Pakistan served as the sample of the study. Interviews and observation were transcribed and analyzed through thematic analysis while the data from the survey was processed in SPSS. The Findings from this study reveal the significant role of PBL in generating conflict resolving skills and other soft skills in employees. Keywords: Problem-based learning, Skill development, soft skills, traits, workplace, employees JEL Classifications: I2, P36